# Question #f7e76

Feb 2, 2018

$m = - 0.47$

#### Explanation:

The first thing that you need to do here is to distribute the minus sign to all the terms of the equation. Alternatively, you can just cancel out the minus sign on both sides because

$- \left(0.79 m + 0.227\right) = - \left(2.09 m + 0.838\right)$

is equivalent to

$- 1 \cdot \left(0.79 m + 0.227\right) = - 1 \cdot \left(2.09 \cdot m + 0.838\right)$

You will end up with

$\textcolor{red}{\cancel{\textcolor{b l a c k}{- 1}}} \cdot \left(0.79 m + 0.227\right) = \textcolor{red}{\cancel{\textcolor{b l a c k}{- 1}}} \cdot \left(2.09 m + 0.838\right)$

$0.79 m + 0.227 = 2.09 m + 0.838$

Next, subtract $2.09 m$ from both sides of the equation to get all the terms that contain the variable $m$ to one side of the equation.

$0.79 m + 0.227 - 2.09 m = \textcolor{red}{\cancel{\textcolor{b l a c k}{2.09 m}}} + 0.838 - \textcolor{red}{\cancel{\textcolor{b l a c k}{2.09 m}}}$

$- 1.3 m + 0.227 = 0.838$

Subtract $0.227$ from both sides of the equation to get

$- 1.3 m + \textcolor{red}{\cancel{\textcolor{b l a c k}{0.227}}} - \textcolor{red}{\cancel{\textcolor{b l a c k}{0.227}}} = 0.838 - 0.227$

$- 1.3 m = 0.611$

Finally, divide both sides of the equation by $- 1.3$ to isolate $m$.

$\frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{- 1.3}}} m}{\textcolor{red}{\cancel{\textcolor{b l a c k}{- 1.3}}}} = \frac{0.611}{-} 1.3$

$m = - 0.47$